Ḥaz̤rat Amīr H̱usrau aur Ṭonk - Khan, Shaukat Ali (Maulānā Abū-'l-Kalām Āzād ʿArabik Paršiyan Rīsarc Insṭīṭiyūṭ Ṭonk, Rājasthān, 2019)
On the Persian poet Amīr Khusraw Dihlavī, approximately 1253-1325, and his association with Tonk, Rajasthan.
Includes bibliographical references
Keywords: Amīr Khusraw Dihlavī; approximately 1253-1325; Criticism and interpretation.; Tonk (India); Intellectual life.